Exploring the Impact of Academic Reading and Research Competence on Academic Writing: A Multi-Regression Analysis among EFL Undergraduates - Prihandoko, Lastika Ary (Universitas Pendidikan Mandalika, 2024)
In today's academic landscape, enhancing the academic writing proficiency of undergraduate students studying English as a Foreign Language (EFL), particularly in the context of thesis writing, is a paramount concern. This research aims to shed light on the influence of Academic Reading (AR) and Research Competence (RC) on Academic Writing (AW) through a comprehensive analysis employing a multi-regression approach. To achieve this goal, the researcher was conducted a rigorous investigation involving 162 students enrolled in English Literature and English Education departments. The researcher was distributed a structured online questionnaire to gather relevant data, which the researcher subsequently analyzed using SmartPLS 4. The analysis result unveiled a substantial statistical relationship between AR, RC, and AW, with an impressive R-square value of 0.580. This finding underscores the pivotal role played by AR and RC in explaining approximately 58% of the variance in AW. This study represents a critical step forward in comprehending the intricate interplay between AR, RC, and AW. It offers valuable insights into the substantial connections between academic reading, research competence, and academic writing. Importantly, this research provides guidance for educational efforts aimed at enhancing the academic writing capabilities of EFL undergraduates, with a specific focus on the realm of thesis writing.Â